Roberta Falcone e Serena Guarracino (eds.), Terra e parole. Donne / scrittura / paesaggi (Bologna, Ebook @ women, 2016, ISBN 978-88-98880-38-6) (Altre Modernità, 2017)
Roberta Falcone e Serena Guarracino (eds.), Terra e parole. Donne / scrittura / paesaggi(Bologna, Ebook @ women, 2016, ISBN 978-88-98880-38-6)di Anna Vanzan